Connected but Disengaged: Social Media Use and the Decline of Youth Electoral Participation in Indonesia - Toto Sugiarto; Roni Jayawinangun; David Rizar Nugroho; Oky Adrian (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2026)
Indonesia's 2024 elections exposed a paradox at the heart of its digital democracy: youth who are the most connected generation in the nation's history are simultaneously its most disengaged voters. This study examines the relationship between social media use and political participation among Indonesian university students, drawing on an integrated theoretical framework combining political communication theory, the Civic Voluntarism Model (CVM), and networked publics theory. A cross-sectional survey was administered to 551 university students across public and private institutions in West Java, Indonesia. Instruments were validated through confirmatory factor analysis and demonstrated adequate internal consistency (Cronbach's α = .81–.87 across subscales). Results reveal a 13.1 percentage-point decline in voting intention (from 45.6% to 32.5%), alongside critically low online (M = 0.75/5.0) and offline (M = 0.80/5.0) political participation. Despite near-universal platform adoption (WhatsApp: 96.9%; Instagram: 95.5%), political knowledge averaged 2.49/4.0 and failed to translate into action. Spearman correlation and chi-square analyses indicate that political knowledge, trust, and barrier perceptions are significantly associated with participation outcomes. Psychological barriers—political disinterest, news distrust, and fear of political expression—emerged as the dominant suppressors of engagement, rather than logistical constraints. These findings challenge technological determinism and carry implications for communication practitioners, educators, and policymakers seeking to revitalize youth democratic participation.